Library Management Strategies in Improving Student Literacy Quality - Ach. Nadim Mubarok; Ach. Faziku Muhlis; Afifatur Rohmah; Rusdiana Navlia (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze library management strategies for improving student literacy in schools. Literacy is an important skill that encompasses not only reading and writing but also understanding and critically processing information. School libraries play a strategic role as learning resource centers that can support student literacy improvement if managed properly. This study used a qualitative approach with a descriptive approach. Data collection techniques included observation, interviews, and documentation. Data were analyzed using data reduction techniques, data presentation, and conclusion drawing. The results indicate that effective library management strategies include developing relevant collections, improving librarian competency, utilizing information technology, implementing engaging literacy programs, and creating a comfortable library space. Furthermore, supporting factors such as school support and adequate facilities were identified, as well as inhibiting factors such as budget constraints and low student reading interest. Efforts to address these obstacles include increasing policy support for sustainable collection development, librarian training, and collaboration with various parties. With the implementation of appropriate management strategies, school libraries can function optimally in improving student literacy.